2020
DOI: 10.1039/d0nj03095c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights into the allylic oxidation of aliphatic compounds by tetraamido iron(v) species: A C–H vs. O–H bond activation

Abstract: The main challenges in synthetic organic chemistry are chemoselective oxidation of C-H bond by natural complexes under mild conditions. Heme and non-heme metal complexes with several oxidants such as dioxygen,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 139 publications
2
5
0
Order By: Relevance
“…In our previous studies, we performed a method assessment using functionals such as B3LYP, 14 B3LYPD-2, 15 wB97XD, 16 B97D, 15 M06-2X, 17 TPPSh, 18 and MP2 19 and it was found that the B3LYP, B3LYP-D2 and wB97XD functionals predict the correct spin state of transition metal complexes. 10 m ,20 Furthermore, among them, B3LYP-D2 was found to be superior. Thus, we restricted our calculations to the B3LYP-D2 functional.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In our previous studies, we performed a method assessment using functionals such as B3LYP, 14 B3LYPD-2, 15 wB97XD, 16 B97D, 15 M06-2X, 17 TPPSh, 18 and MP2 19 and it was found that the B3LYP, B3LYP-D2 and wB97XD functionals predict the correct spin state of transition metal complexes. 10 m ,20 Furthermore, among them, B3LYP-D2 was found to be superior. Thus, we restricted our calculations to the B3LYP-D2 functional.…”
Section: Computational Detailsmentioning
confidence: 99%
“…S1 and Table S2 of ESI †). 14 S4 of ESI †). Upon moving rightwards in the Periodic Table from Cr to Mn and Fe, one and two extra electrons are added into the d orbital, respectively, whereas the pairing of electrons takes place in Co, Ni, and Cu species.…”
mentioning
confidence: 99%
“…S1 and Table S2 of ESI†). 14 Spin natural orbital (SNO) analysis showed the transfer of an electron to the metal d orbital (Fig. S4 of ESI†).…”
mentioning
confidence: 99%
“…Based on earlier theoretical and experimental studies, a mechanism for the generation of metal(IV)-oxo and metal(V)oxo species from metal(III)-hydroperoxo species is shown in Scheme S1 of the ESI. † 5,66,[90][91][92][93] This mechanism is based on O⋯O bond cleavage, either homolytic or heterolytic. Homolytic cleavage gives the metal(IV)-oxo species and the heterolytic cleavage gives metal(V)-oxo species along with OH • / OH − , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Based on earlier theoretical and experimental studies, a mechanism for the generation of metal( iv )–oxo and metal( v )–oxo species from metal( iii )-hydroperoxo species is shown in Scheme S1 of the ESI † 5,66,90–93 . This mechanism is based on O⋯O bond cleavage, either homolytic or heterolytic.…”
Section: Resultsmentioning
confidence: 99%